Automatic check for the certification label - Čambál, R.; Sýkora, T. (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2022)
The subject of this article is to propose quality improvement in the field of automated control of presence/absence of the certification label for car seats intended for Chinese market, with the introduction of quality inspection of the label and inspection of the correct affixietion position at a defined seat position. The main benefit of this work is to apply a measurement process using Poka-Yoke control by automating the process at Lear Corporation Seating Slovakia s.r.o..
Keywords: quality; automation; control; process; sensor; Poka-Yoke competition